2020
DOI: 10.3390/jcm9113436
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Discontinuation of Structured Exercise Programme in Chronic Fatigue Syndrome Patients

Abstract: Purpose: The purpose of this study was to assess differences in the physiological profiles of completers vs. non-completers following a structured exercise programme (SEP) and the ability to predict non-completers, which is currently unknown in this group. Methods: Sixty-nine patients met the Fukuda criteria. Patients completed baseline measures assessing fatigue, autonomic nervous system (ANS), cognitive, and cardiovascular function. Thirty-four patients completed a home-based SEP consisting of 10–40 min per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 39 publications
0
11
0
1
Order By: Relevance
“…In a previous study, we noted that CFS patients who completed the IAP showed improved visual attention both in terms of reaction time and correctness of responses and processing speed of simple visual stimuli [ 34 ]. It is important to note that there was a significant drop out rate of 51% with IAP [ 49 ]. The more sympathetic drive contributes to the control of blood vessels, the longer the reaction time with simple visual stimuli and the lower the HRmax during physical exercise, the chance of a CFS patient completing IAP was reduced [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, we noted that CFS patients who completed the IAP showed improved visual attention both in terms of reaction time and correctness of responses and processing speed of simple visual stimuli [ 34 ]. It is important to note that there was a significant drop out rate of 51% with IAP [ 49 ]. The more sympathetic drive contributes to the control of blood vessels, the longer the reaction time with simple visual stimuli and the lower the HRmax during physical exercise, the chance of a CFS patient completing IAP was reduced [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that there was a significant drop out rate of 51% with IAP [ 49 ]. The more sympathetic drive contributes to the control of blood vessels, the longer the reaction time with simple visual stimuli and the lower the HRmax during physical exercise, the chance of a CFS patient completing IAP was reduced [ 49 ]. Overall, it could be concluded that an aerobic activity programme characterised by a high frequency of weekly training sessions (5 times/week) and incremental progression of exercise intensity is not well tolerated by a significant number of CFS patients (51% of the patients in the current study).…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be underlined that physical exercise programme in ME/CFS might be deleterious to some patients. Fifty one percent of dropout rate was noted due to post-exertional malaise (PEM) perceived by CFS patients undergoing physical activity programme based on aerobic physical activity [35]. CFS patients with higher severity of disturbance in autonomic control over blood vessels, worse cognitive function and the lower the maximal Heart Rate during physical exercise had lower chance of completion of programme based on physical activity [35].…”
Section: Long Covid Therapymentioning
confidence: 99%
“…Fifty one percent of dropout rate was noted due to post-exertional malaise (PEM) perceived by CFS patients undergoing physical activity programme based on aerobic physical activity [35]. CFS patients with higher severity of disturbance in autonomic control over blood vessels, worse cognitive function and the lower the maximal Heart Rate during physical exercise had lower chance of completion of programme based on physical activity [35]. Therefore, If above described suggestions on parallels between pathophysiology of ME/CFS and long COVID would be confirmed in further researches, then reactions of long COVID patients on rehabilitation based on physical activity programmes should be closely monitored due to risk of PEM occurrence.…”
Section: Long Covid Therapymentioning
confidence: 99%
See 1 more Smart Citation